Professional networks and the labour market assimilation of immigrants - Olof Åslund; Mattias Engdahl; Sébastien Willis (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2024)
We study how professional networks are related to immigrant labour market integration. Matched employer-employee data for Sweden show that networks grow with time in the host country and that their composition changes from immigrant toward native network members. A firm-dyadic analysis of re-employment of displaced workers suggests that conational connections have a much larger positive effect than native connections. However, the employment effect of native connections grows with years since migration. Furthermore, native connections tend to be associated with higher earnings and increased hires in connected local industries. After 20 years in Sweden, the built-up connections raise immigrant re-employment rates by 0.7 to 1.1 percentage points, amounting to 10-20 percent of the observed difference by years since migration. Our findings indicate complete assimilation in the total productivity of professional connections for displaced workers.
Keywords: J60; J20; J15; 330; labour market integration of immigrants; networks; job search